Answer:
sorry I don't speak that language
Answer:
y = -(2/3)x + 3
C
Step-by-step explanation:
The slope of the equation that was given is - 2/3
The slope in a slope intercept equation is the number in front of the x when the value of the number in front of the y = 1 and x and y are on opposite sides of the equal sign. Let's translate that.
The original equation is y = -(2/3)x + 5/3
- y and x have to be on opposite sides of the equal sign [They are]
- The slope is the number in front of the x. That's (-2/3). That makes A incorrect.
Now you need to use the given point
The point is (-3 , 5) Put this into the equation that you have so far
y = (-2/3)x + b
y = 5
x = -3
5 = (-2/3)(-3/1) + b Substitute in the givens
5 = (-2 * -3)/3 + b Multiply -2 * - 3 = 6
5 = 6/3 + b Divide the 6 by 3
5 = 2 + b Divide
5 - 2 = b Subtract 2 from both sides
3 = b Switch sides
b = 3
Answer y = (-2/3)x + 3 or C
A= (a+b+c)h is the formula. I hope this is helpful for you. I am pretty positive it will help.
Answer:
(-4, -2)
Step-by-step explanation:
A = (-1, 2)
Add (-3, -4) to that and you get ...
A' = (-1-3, 2-4) = (-4, -2) . . . . matches the last choice
__
The translation function has the effect of moving the point left 3 and down 4. You can count grid squares on the graph to see that A' ends up at (-4, -2).